Interrupting base-mediated benzofuran ring transformation with michael acceptors - Srinivas, Kolluru; Sharma, Rashmi; Ramana, Chepuri V. (Journal of Organic Chemistry, 2017)
A simple two-stage approach for the synthesis of 3-(2-arylbenzofuran-3-yl)propanoates and propanamides has been developed employing simple acrylates and acrylamides and readily available 3-aroylbenzofurans. The key step of this process involves a base-mediated ring opening of the 3-aroylbenzofurans and subsequent Michael addition of the resulting 1,3-dicarbonyl intermediate with acrylate/acrylamide, followed by the deformylation in one-pot. The resulting products undergo an acid-mediated dehydrative cyclization to arrive at these targets.
Keywords: Acyl Benzylic Bromides; Beta-Ketoaldehydes; Efficient Synthesis; Ortho-Hydroxybenzyl Ketones; Phenols; Position; Precursors; Sur Le Benzofuranne; Transposition

Discovery and biological evaluation of nitrofuranyl-pyrazolopyrimidine hybrid conjugates as potent antimicrobial agents targeting Staphylococcus aureus and methicillin-resistant S. aureus - Saini, Sapna; Reddy, G. Lakshma; Gangwar, Anjali; Kour, Harpreet; Nadre, Gajanan G.; Pandian, Ramajayan; Pal, Sunny; Nandi, Utpal; Sharma, Rashmi; Sawant, Sanghapal D. (RSC Medicinal Chemistry, 2025)
Nitrofuran and pyrazolopyrimidine-based compounds possess a broad antimicrobial spectrum including Gram-positive and Gram-negative bacteria. In the present work, a series of conjugates of these scaffolds was synthesized and evaluated for antimicrobial activity against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). Many compounds showed MIC values of <= 2 mu g ml-1, with compound 35 demonstrating excellent activity (MICs: 0.7 and 0.15 mu g ml-1 against S. aureus and MRSA, respectively) and safety up to 50 mu g ml-1 in HepG2 cells. Compound 35 also exhibited no hemolytic activity, biofilm eradication, and effectiveness against efflux-pump-overexpressing strains (NorA, TetK, MsrA) without resistance development. It showed synergistic effects with vancomycin (S. aureus) and rifampicin (MRSA). Mechanistic studies revealed that compound 35 exhibits good membrane-targeting abilities, as evidenced by DAPI/PI staining and scanning electron microscopy (SEM). In an intracellular model, it reduced bacterial load efficiently in both S. aureus and MRSA strains. With a strong in vitro profile, compound 35 demonstrated favorable oral pharmacokinetics at 30 mg kg-1 and potent in vivo anti-MRSA activity, highlighting its potential against antibiotic-resistant infections.

Elucidating the potential of novel class biphenyl-phenyl acetate, IDD-AN-A1, an inhibitor targeting Isocitrate Lyase in Mycobacterium tuberculosis: a target to lead approach - Negi, Anjali; Perveen, Summaya; Kour, Harpreet; Sawant, Sanghapal D.; Sharma, Rashmi (Bioorganic Chemistry, 2026)
Isocitrate lyase (ICL), a pivotal enzyme of the glyoxylate shunt pathway in Mycobacterium tuberculosis (Mtb), represents an attractive target for the development of new anti-tuberculosis (TB) therapeutics. In this study, we identified 2-methoxy-4-((nitrosooxy)methyl)phenyl 2-(2-fluoro-[1,1 `-biphenyl]-4-yl)propanoate (IDDAN-A1) as a potent inhibitor of Mtb ICL. The compound exhibited strong activity against Mtb, with a minimum inhibitory concentration of 6.25 mu g/mL, and demonstrated potent inhibition in enzyme-based assays targeting ICL. Molecular docking studies further supported Mtb ICL as the potential molecular target of this compound. Cytotoxicity and hemolytic assays revealed a favorable safety profile for the compound with selectivity index >10. In combination studies, it exhibited additive and synergistic activity with the frontline drug Rifampicin and Delamanid respectively. Additionally, ex vivo assays simulating the intracellular environment of the pathogen demonstrated strong inhibitory potency. In vitro inhibition studies further confirmed the bacteriostatic nature of the compound across different concentrations. Collectively, these findings demonstrate that this molecule possesses promising anti-tuberculosis activity by targeting the ICL enzyme in Mtb.
Keywords: Anti-tuberculosis activity; Ex vivo; Isocitrate lyase; tuberculosis